EMPIRISISME, SEBUAH PENDEKATAN PENELITIAN ARSITEKTURAL - Sativa Sativa (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2011)
Empirisism is a paradigm in science philosophy which influences variouskind of research methods, include architectural researches. Using content analysis,this paper aimed to explore empirisism, from many aspects. Those are historydevelopment, characteristics, levels, and also relation of empirisism with otherparadigm, especially rasionalism. In architectural research, empiricism commonlynamed as naturalistic method.This paper concluded that besides has manyimportant roles, empirism also has weakness, so it is better to develop researchesby using both of those paradigms, empirism and rasionalism, especially inarchitectural researches.Keywords: empiricism, paradigm, rasionalism